2018
DOI: 10.5720/kjcn.2018.23.6.516
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 24-hour Diet Recalls for Estimating Energy Intake in Elderly Men using the Doubly Labeled Water Method

Abstract: Objectives: This study assessed the accuracy of the 24-hour diet recall method for estimating the energy intake of elderly men using the doubly labeled water as a reference method. Methods: Seventeen subjects (mean age 72.5 ± 3.9 years), who maintained the same body weight during the two weeks study period, were included in this study. Three 24hour diet recalls (two weekdays and one weekend) were obtained over a 14 day period to estimate the mean energy intake. The total energy expenditure was measured over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Johnson et al .’ study [ 42 ] that evaluated the accuracy of the three-day meal recording method in elderly persons reported underreporting in energy intakes in men and women of 12% and 24%, respectively, whereas in another study [ 43 ] conducted on elderly persons, the rates were 12% for men and 31% for women. Furthermore, studies conducted in Korea on elderly women [ 22 ] and men [ 23 ] also reported that TEI underreported TEE by 25.9% and 4.4%, respectively. Although these studies were conducted in the elderly, their results support our findings, which indicates that 24-h dietary recall underreports energy intakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson et al .’ study [ 42 ] that evaluated the accuracy of the three-day meal recording method in elderly persons reported underreporting in energy intakes in men and women of 12% and 24%, respectively, whereas in another study [ 43 ] conducted on elderly persons, the rates were 12% for men and 31% for women. Furthermore, studies conducted in Korea on elderly women [ 22 ] and men [ 23 ] also reported that TEI underreported TEE by 25.9% and 4.4%, respectively. Although these studies were conducted in the elderly, their results support our findings, which indicates that 24-h dietary recall underreports energy intakes.…”
Section: Discussionmentioning
confidence: 99%
“…We surveyed the TEI of the study subjects using a 24-h diet recall method for 3 non-continuous days (2 weekdays and 1 weekend day) within 2 weeks of DLW measurements. Trained investigators conducted the interviews by applying KHNANES guidelines [ 23 ]. On the days, dietary data were collected, meals and drinks consumed by subjects during the preceding 24 h were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most side dishes are shared rather than served individually. No studies have assessed the validity of food records in Korea, and few studies have assessed the accuracy of 24-h recalls in Koreans [ 9 10 ]. Recently, the accuracy was tested in older Korean men and women using the doubly labeled water method for reported energy intake [ 9 10 ], but not for other nutrients or food groups.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have assessed the validity of food records in Korea, and few studies have assessed the accuracy of 24-h recalls in Koreans [ 9 10 ]. Recently, the accuracy was tested in older Korean men and women using the doubly labeled water method for reported energy intake [ 9 10 ], but not for other nutrients or food groups. Dietary patterns and food intake, in addition to nutrient intake, are important in nutrition research but the accuracy of food records according to food groups has not been assessed in Koreans.…”
Section: Introductionmentioning
confidence: 99%